(untitled) (Global Journal of Science Frontier Research, 2014)
This paper examines the effect of urbanization on house rent in Ilorin Nigeria. It appraises the level of urbanization in Ilorin under historical periods of pre-colonial, colonial and post-colonial era. The data used for the study were obtained from random sampling of 150 household in the metropolitan area of Ilorin. The information on the trend of house rent for period of ten years (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) were obtained through structured questionnaire administered in the study area. Multiple regression analysis was used to examine relationship between urbanization and house rent. Findings from this study show that there was relatively slow urban growth in the pre-colonial era. Colonial period witnessed a relatively phenomenal growth, while post-colonial era recoded a high level of urban growth in terms of population and land consumption. Also, results from regression analysis shows a significant relationship between urbanization and house rent at F-value of 216.535 and P-value of 0.000 (p